2019
DOI: 10.5539/gjhs.v11n8p96
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Use of Birth Control Methods for Family Planning by Married People in Nsukka Education Zone of Enugu State

Abstract: OBJECTIVE: The study investigated the knowledge level and use of birth control methods by married people for family planning in Nsukka Education Zone of Enugu state. MATERIALS & METHODS: The population of this study comprised 4450 married people who registered for marriage from 2010 to 2017 in Nsukka Education Zone of Enugu State. The sample was 445 respondents (210 married males and 235 married females). The instrument for data collection was a questionnaire titled: Knowledge and use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…A retrospective study in India of 200 DMPA injectable contraceptive users stated that persistent contraceptive use occurred in acceptors who had been effectively counseled (Fonseca et al, 2017a). This proves that the provision of effective education and counseling will increase mother's knowledge about the importance of contraception and can avoid the possibility of non-compliance in obtaining contraceptive services (Ogidi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study in India of 200 DMPA injectable contraceptive users stated that persistent contraceptive use occurred in acceptors who had been effectively counseled (Fonseca et al, 2017a). This proves that the provision of effective education and counseling will increase mother's knowledge about the importance of contraception and can avoid the possibility of non-compliance in obtaining contraceptive services (Ogidi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A comparable study conducted in Ethiopia found that a desire for more children was a prevalent reason for not using family planning (31). Moreover, a study conducted among Igbo women in Southeast Nigeria identi ed spousal rejection of family planning as the most common reason for nonuse (32). Additionally, previous research has revealed that there is a resistance to family planning in Ghana that is rooted in attitudes, as well as a growing tendency to be wary of potential side effects (33,34).…”
Section: Discussionmentioning
confidence: 99%